Factors Associated with Retained Placenta: A Case-Control at Bethesda Hospital Yogyakarta - Ruth P. Gitasari; Theresia A.R. Kusumosih; Daniel C.A. Nugroho; H. Rahardjo (Faculty of Medicine Universitas Kristen Duta Wacana, 2022)
Background The retained placenta is a common cause of postpartum bleeding. Many conditions commonly can be found in pregnant women cause retained placenta.Objective This study aims to identify factors associated with retained placenta.Method This study was performed as an observational analytic study with a case-control method. The data used is secondary data, using normal postpartum mothers (n=74) and postpartum women diagnosed with the retained placenta (n=37) medical records, at Bethesda Hospital from 2013 until 2018. Variables were analyzed using simple logistic regression to measure crude odds ratio and using multiple logistic regression to calculate adjusted odds ratio.Results The factor associated with retained placenta was preterm labor (OR 37.16; CI 95% 6.98-197.84). Age (OR 1.32; CI 95% 0.34-5.19), anemia in pregnancy (OR 2.43; CI 95% 0.83-7.14), history of previous cesarean section (OR 9.63; CI 95% 0.79-117.36), history of curettage (OR 3.65; CI 95% 0.93-14.37) and parity (OR 2.07; CI 95% 0.72-5.98) increasing risk to develop retained placenta, but not statistically significant.Conclusion A history of previous cesarean section and preterm labor statistically increases the risk of retained placenta in Bethesda Hospital Yogyakarta. Age, anemia in pregnancy, and history of curettage were clinically associated with retained placenta, but not statistically significant.